Carotid Endarterectomy Following Intravenous Thrombolysis in the UK. (July 2021) - Johal, Amundeep S.; Naylor, A. Ross; Pherwani, Arun D.; Li, Qiuju; Birmpili, Panagiota; Waton, Sam; O'Neill, Richard; Boyle, Jonathan R.; Cromwell, David A.
Abstract : Objective: The aim of this study was to evaluate the effect of pre-operative intravenous thrombolytic therapy (ivTT) on short term outcomes after carotid endarterectomy (CEA) among patients who presented with ischaemic stroke. Methods: A retrospective study using a large population based dataset from the National Vascular Registry in the United Kingdom (UK-NVR). The cohort included adult patients who underwent CEA for ischaemic stroke between 1 January 2014 and 31 December 2019. NVR records provided information on patient demographics, Rankin score, medication, time from onset of symptoms to surgery and whether the patient received ivTT prior to surgery. Logistic regression was used to evaluate the relationship between ivTT and rates of any stroke at 30 days after CEA and in hospital complication rates for neck haematoma. Secondary outcomes included in hospital cardiac and respiratory complications, and cranial nerve injury. Results: Between 2014 and 2019, 9 030 patients presented with a stroke and underwent CEA, of whom 1 055 (11.7%) had received pre-operative ivTT. Those receiving ivTT were younger (mean 70.6 vs. 72.0 years, p < .001). The median (IQR) time from symptom to CEA was 10 days (6 – 17) for ivTT patients and 11 days (7 – 20) for CEA patients not receiving ivTT. Post-operative rates of 30 day stroke were similar between the no ivTT (2.1%) and ivTT (1.8%) cohorts ( p = .48). In hospital neck haematomas were statistically significantly more common in CEA patients receiving ivTT (3.7%) vs. no ivTT (2.3%) ( p = .006). There was no statistically significant association between 30 day stroke and neck haematoma complications when stratified for delays from symptom onset to CEA, but the overall cohort contained few adverse events for analysis during the very early time period. Conclusion: The use of ivTT before CEA in stroke patients was not associated with an increased risk of 30 day stroke, but there was an increase in the risk of neck haematoma.